STRATEGIC CLARITY AND ITS FUNCTION IN DEVELOPING THE DIGITAL STRATEGY: AN ANALYTICAL STUDY OF THE VIEWPOINTS OF A SAMPLE OF ACADEMIC LEADERS AT THE UNIVERSITY OF KUFA - Ikram Adnan Al-Dhalim (Universitas Negeri Malang, 2026)
This study looks at how well a strategy is defined affects the development of digital approaches at Kufa University. Three elements—clear goals, well-defined activities and procedures, and efficient resource allocation—defined strategic clarity; the digital plan covered topics including digital infrastructure, digital culture, and innovation in the digital sphere. A descriptive-analytical technique was used and academic leaders—deans, associate deans, and heads of departments—were surveyed. Out of 95 questionnaires sent, 93 legitimate responses were returned and examined using SPSS program. The results showed that participants showed great levels of digital strategy as well as strategic clarity. The results also showed a major beneficial link between strategic clarity and digital strategy (r = 0.871, p < 0.01). Furthermore, regression analysis confirmed that strategic clarity significantly influences digital plans and explains 75.9% of their variation (R² = 0.759). Among the several facets of strategic clarity, the clearest link to digital strategy shown was objectives' clarity. The study finds that increased strategic clarity is essential for accelerating digital transformation efforts and improving the results of online projects in higher education institutions.